2015
DOI: 10.3390/s150923402
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Sensing of In-Ear Pressure for Heart Rate Monitoring with a Piezoelectric Sensor

Abstract: In this study, we developed a novel heart rate (HR) monitoring approach in which we measure the pressure variance of the surface of the ear canal. A scissor-shaped apparatus equipped with a piezoelectric film sensor and a hardware circuit module was designed for high wearability and to obtain stable measurement. In the proposed device, the film sensor converts in-ear pulse waves (EPW) into electrical current, and the circuit module enhances the EPW and suppresses noise. A real-time algorithm embedded in the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 24 publications
(28 reference statements)
1
57
0
Order By: Relevance
“…HR measurements between ECG and earpiece HR monitor almost completely overlapped each other (Leboeuf, et al, 2014). In addition, Park et al (2015) identified an earpiece HR monitoring device to be VOLUME 13 | ISSUE 3 | 2018 | 533 significantly accurate across various intensities of exercise. However, several limitations may occur with earpiece devices, including skin irritation, difficulties connecting to additional devices, bulky sensors and hygiene (Chan, Estève, Fourniols, Escriba, & Campo, 2012).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…HR measurements between ECG and earpiece HR monitor almost completely overlapped each other (Leboeuf, et al, 2014). In addition, Park et al (2015) identified an earpiece HR monitoring device to be VOLUME 13 | ISSUE 3 | 2018 | 533 significantly accurate across various intensities of exercise. However, several limitations may occur with earpiece devices, including skin irritation, difficulties connecting to additional devices, bulky sensors and hygiene (Chan, Estève, Fourniols, Escriba, & Campo, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…The absence of bone and predominantly compromising of cartilage and blood suggests the ear is suitable for continuous HR monitoring with photoplethysmography (PPG) (Budidha & Kyriacou, 2014;Park, Jang, Park, & Youm, 2015). The length of the ear canal is roughly 2.5cm, with a diameter of approximately 7mm with exceedingly sensitive skin, (Park et al, 2015), with PPG technology, the earpiece sensors detect how much light is reflected from the subcutaneous blood vessels (Budidha & Kyriacou, 2014). PPG uses optoelectronic features to isolate red and infrared wavelengths and light refraction to dictate blood flow (Schafer & Vagedes, 2013;Spierer, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various applications have been developed to measure vital signs by means of piezoelectric material45678. A piezoelectric based system has been developed to monitor respiration rate7, heart rate456, and seismocardiography8.…”
mentioning
confidence: 99%
“…A piezoelectric based system has been developed to monitor respiration rate7, heart rate456, and seismocardiography8. This paper presents a novel technique for the reconstruction of the ECG corresponding signal from a measured piezoelectric output voltage signal.…”
mentioning
confidence: 99%